The Taguchi technique of the transplanted kidney ureter implantation - single centre experience - Pacovský, Jaroslav; Navrátil, Pavel (Upsala journal of medical sciences, 2007)
Taguchi technique of ureteral implantation was used in 22 kidney transplant patients (group T). Group T was compared with 25 patients who were treated using Lich-Gregoir technique (group LG). Immunosuppression, incidence of biopsy evidenced acute cellular rejection (ACR), haematuria rate and ureteral complications (stricture, reflux) were assessed in both groups. The immunosuppression used was based on cyclosporin A (63.6%), tacrolimus (27.3%) and sirolimus (8.1%) in T group. Cyclosporin A(72%), tacrolimus (20%) and sirolimus (8%) were used in LG group. No induction was used. The incidence of ACR was similar in both groups--T resp. LG was 50% resp. 52%. Haematuria after operation was on average 4.0 days in the T group and on average 3.1 in the LG group. Ureteral complications were observed in 18.2% of cases in T group and in 16% of cases in LG group. No reflux was evidenced in any group. Taguchi technique is fast and very easy to do. A slightly higher incidence of ureteralcomplications and a longer period of postoperative haematuria were observed in T group. Taguchi technique is very easily performed with a shorter operating time. We advocate it as a method of ureteral implantation on the thin-wall urinary bladder. The results were very good in these cases.
Keywords: Immunosuppressive Agents; urologické chirurgické výkony; studie případů a kontrol; Ureter; Treatment Outcome; Urologic Surgical Procedures; lidé; Case-Control Studies; ureter; Humans; imunosupresiva; výsledek terapie